DAMPAK SOSIAL PENUTUPAN LOKALISASI - Mu'man Nuryana (Sosio Informa, 2003)
Kasus Sunan Kuning Semarang ( Social Impacts from the Closing of Official ProstitutionComplexes: Case Study in Sunan Kuning Semarang).Indonesian ambiguous policy on prostitution issue has been affirmed by the creation of'Lokalisasi' (official prostitution complexes). Lokalisasi has been used as a model by local governments to alleviate the impact of harms from prostitution. It is very important then, to look how this social experiment has failed to alleviate the harms of prostitution by going down the legalization track. However, this policy emerged in response to the growing demand from local community to stop Lokalisasi. These harms have increased and significant new harms have joined them such as the traffic in young women in Indonesia. This research has found some valuable results that Lokalisasi should not be considered as a silver bullet to alleviate prostitution problems, but it is assumed to be a solution of minimizing its impacts to society. Such a Lokalisasi should not be placed in the residential area, rather it should be placed in business district in the down-town of the city to which anyone easily able to reach it.Key Words: Official prostitution complexes, Lokalisasi, Mutual consent, Decriminalization prostitute